Empiricism and analytical tools for 21 Century applied linguistics - ELORZA, Izaskun; CARBONELL I CORTÉS, Ovidi; ALBARRÁN, Reyes; GARCÍA RIAZA, Blanca; PÉREZ-VENEROS, Miriam (Colección de libros electrónicos en Xebook, 2012)
The present volume follows an open-access publication policy, offering access to the multimedia files of the plenary lectures whose authors agreed to their publication and the Language Learning special roundtable, as well as a selection of the written versions of the papers presented at the 29th International Conference of the Spanish Association of Applied Linguistics (AESLA), 86 of which were accepted for publication after a double-blind selection process and are collected in this volume.